ANALISIS KINERJA AGROINDUSTRI CRUDE COCONUT OIL (CCO) PADA IKRT “SUMBER REZEKI” DI DESA TINABOGAN KECAMATAN DONDO KABUPATEN TOLITOLI - Mulkiah Amal Basri; Asriani Hasanuddin; Lien Damayanti (Universitas Tadulako, 2018)
This study is a case study on the performance of crude coconut oil (CCO) agroindustry business run by Tinabogan Village community through a small household industrygroup SumberRezeki which is one of the developments of integrated coconut industry byTolitolidistrict government of Central Sulawesi. This study aimed to analyze the two-year performance of the group